Neural Basis of Tics: A Functional MRI Study - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Event-related functional MRI (fMRI) was used to study the neural basis of spontaneous motor and vocal tics in 10 patients with Tourette syndrome, at the National Institute of Neurological Disorders and Stroke, Bethesda, MD.